Identifikasi Bakteri dan Penentuan Jumlah Koloni pada Masker Sekali Pakai Berdasarkan Lama Waktu Pemakaian - Ni Putu Widayanti; Ayu Saka Laksmita W; Desak Putu Risky Vidika Apriyanthi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Prolonged use of disposable masks can increase bacterial accumulation due to exposure to droplets, aerosols, and respiratory humidity. This study aims to identify the types of bacteria and determine the number of bacterial colonies on disposable masks based on the duration of use by educational laboratory staff at Bali International University. This study used an analytical observational design with a cross-sectional approach. Samples consisted of 15 disposable masks grouped by duration of use: 3 hours, 6 hours, and 9 hours, with 5 samples each. Examination was carried out through bacterial culture, microbiological identification, and total plate count calculation. The results showed that the number of bacterial colonies increased with increasing duration of mask use. The average total plate count at 3 hours of use was 31.00 ± 9.62 CFU/g, increased to 138.00 ± 33.47 CFU/g at 6 hours, and reached 646.00 ± 122.39 CFU/g at 9 hours. The dominant bacteria found were Bacillus sp. and Staphylococcus sp., with Bacillus sp. dominating across all sample groups. This study concluded that the longer disposable masks were used, the higher the number of bacterial colonies accumulated. Regular mask replacement every 4–6 hours is recommended to maintain hygiene and safety in the laboratory.